Mucoadhesive buccal films containing phospholipid-bile salts-mixed micelles as an effective carrier for Cucurbitacin B delivery. (May 2015) - Lv, Qingyuan; Shen, Chengying; Li, Xianyi; Shen, Baode; Yu, Chao; Xu, Pinghua; Xu, He; Han, Jin; Yuan, Hailong
Abstract Cucurbitacin B (Cu B), a potent anti-cancer agent, suffers with the problems of water-insoluble, gastrointestinal side effects and non-specific toxicity via oral administration and drawbacks in patient's compliance and acceptance through injections. An integration of nanoscale carriers with mucoadhesive buccal films drug delivery system would resolve these issues effectively with greater therapeutic benefits and clinical significance. Thus, the drug loaded mucoadhesive buccal film was developed and characterized in this study and the carboxymethyl chitosan (CCS) was chosen as a bioadhesive polymer, glycerol was chosen as a plasticizer and phospholipid-bile salts-mixed micelles (PL-BS-MMs) was selected as the nanoscale carriers. The CCS-films containing Cu B loaded PL-SDC-MMs was evaluated for the mechanical properties, mucoadhesion properties, in vitro water-uptake, in vitro release and morphological properties, respectively. The optimal CCS-films containing Cu B loaded PL-SDC-MMs was easily reconstituted in a transparent and clear solution with spherical micelles in the submicron range. The in vivo study revealed a greater and more extended release of Cu B from nanoscale CCS-films compared to that from a conventional CCS films (C-CCS-films) and oral marketed tablet (Hulusupian). The absorption of Cu B from CCS-films containing Cu B loaded PL-SDC-MMs resulted in 2.69-fold increased in bioavailability as compared to conventional tablet formulation and 10.46 times with reference to the C-CCS-films formulation. Thus, this kind of mucoadhesive buccal film might be an alternative safe route for delivery of Cu B with better patient compliance and higher bioavailability for the treatments.